An approach to extracting interschema properties from XML schemas at various "severity" levels - De Meo, Pasquale (Informatica (Ljubljana), 2007)
This paper presents an approach for the semi-automatic, uniform extraction of synonymies, hyponymies, overlappings and homonymies holding amoung concepts of different XML schemas. The proposed approach is specialized for XML, is almost automatic and "light". A a further, original, peculiarity, it is parametric w.r.t. a "severity level" against which the extraction task is performed. First the paper presents an overview of the interschema property extraction approaches already presented in the past, as well as a set of criteria for classifying this kind of approaches. After this, it describes the proposed approach in all details, illustrates various theoretical results, presents the experiments we have performed for testing it and compares it with the interschema property extraction previously proposed in the literature.
Keywords: informatika; information science; Extensible Markup Language; XML; sinonimi; homonimi